Pengaruh Latihan Target Menggunakan Kaki Bagian Dalam Terhadap Akurasi Shooting Bagi Atlet Tim Futsal SMAN 1 Kadugede - Didi Muhtarom; Dani Nurdiansyah; Dede Nurohman (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Introduction. This research was carried out because the futsal team athletes at SMAN 1 Kadugede were less enthusiastic and interested in the training methods provided so the training was less than optimal. This study aims to determine the effect of target training using the inside of the foot on shooting accuracy in athletes from the futsal team at SMAN 1 Kadugede. Method. The type of research used in this research is experimental and one group pretest posttest research design so that all samples receive treatment. The treatment given by researchers was 12 meetings with a frequency of 2 times a week. Sampling in this study used total sampling, so that there were 20 athletes from the SMAN 1 Kadugede Futsal Team. The research instrument used in this study was a shooting accuracy test using the inside of the foot towards a predetermined target in the goal area. Data analysis used the t test (paired sample t test) with a significance level of 0.05 using SPSS 26 software. Results. The results of the research that has been carried out show that there is a significant increase, from the mean pretest result of 20.00 and posttest of 22.35, there is an increase with a difference of 2.35. Conclusion. The results of this research prove that target training using the inside of the foot on shooting accuracy for athletes from the futsal team at SMAN 1 Kadugede has a significant influence.